All-inorganic perovskite nanocrystal assisted extraction of hot electrons and biexcitons from photoexcited CdTe quantum dots. Issue 2 (13th December 2017) - Mondal, Navendu; De, Apurba; Samanta, Anunay
Abstract : Harvesting of hot electrons and biexcitons from CdTe quantum dots by all-inorganic perovskite nanocrystals is demonstrated through femtosecond transient absorption measurements. Abstract : Excitation of semiconductor quantum dots (QDs) by photons possessing energy higher than the band-gap creates a hot electron–hole pair, which releases its excess energy as waste heat or under certain conditions (when hν > 2 E g ) produces multiple excitons. Extraction of these hot carriers and multiple excitons is one of the key strategies for enhancing the efficiency of QD-based photovoltaic devices. However, this is a difficult task as competing carrier cooling and relaxation of multiple excitons (through Auger recombination) are ultrafast processes. Herein, we study the potential of all-inorganic perovskite nanocrystals (NCs) of CsPbX3 (X = Cl, Br) as harvesters of these short-lived species from photo-excited CdTe QDs. The femtosecond transient absorption measurements show CsPbX3 mediated extraction of both hot and thermalized electrons of the QDs (under a low pump power) and (under a high pump fluence) extraction of multiple excitons prior to their Auger assisted recombination. A faster timescale of thermalized electron transfer (∼2 ps) and a higher extraction efficiency of hot electrons (∼60%) are observed in the presence of CsPbBr3 . These observations demonstrate the potential of all-inorganic perovskite NCs in the extraction of these short-lived energy rich species implying that complexes of the QDs and perovskite NCs are better suited for improving the efficiency of QD-sensitized solar cells.